FEASIBILITY STUDY OF CNC MACHINE INVESTMENT TO OPTIMIZE MAIN WORKSHOP OPERATIONS AT PT BUKIT ASAM TBK - Rizki Satriawan; Oktofa Yudha Sudrajad (Journal of Economic, Bussines and Accounting (COSTING), 2025)
PT Bukit Asam Tbk (PTBA), a company operating in the coal mining industry, is currently facing challenges in improving operational efficiency, especially in the maintenance and repair activities at the Coal Handling Facility (CHF). The increasing demand for components and spare parts reveals the shortcomings of conventional machinery in terms of precision, productivity, and cost-effectiveness. In response, PTBA is exploring the possibility of investing in Computer Numerical Control (CNC) machines to enhance output and lower long-term operational costs. This study investigates the feasibility of such an investment using capital budgeting techniques, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), and Profitability Index (PI). To further examine potential uncertainties, a risk assessment was carried out through sensitivity analysis and Monte Carlo simulation. The findings show that the investment is financially sound, generating an NPV of IDR 5.26 billion, an IRR of 18%, and a payback period of 6 years and 4 months, with a 93.7% likelihood of achieving a positive return. With proper execution—such as optimizing production processes, maximizing machine utilization, and providing adequate workforce training—the CNC machine investment is anticipated to significantly improve operational performance, reduce dependency on third-party suppliers, and support PTBA’s long-term strategic goals.